Development of Islamic Values Civics Module on Rights and Obligations for Elementary High School Students - Melyani Sari Sitepu; Chairunnisa Amelia (Nazhruna: Jurnal Pendidikan Islam, 2021)
This article aims to develop a Civics module with Islamic values ​​on the rights and obligations of high school students in elementary schools. This research is development research (R&D). This research uses a development research model. The steps in this research are: (1) potential and problems, (2) data collection, (3) product design, (4) module validation, (5) module design revision, (6) limited module trial, (7 ) Revision of modules, (8) The final product of the Civics module has Islamic values ​​that meet the valid and practical criteria. The development process includes product design and product validation. Data collection techniques used in this study were observation and questionnaires. The results of this study indicate that the PPKn module has Islamic value. The material of rights and obligations developed has met the very valid criteria. This is evidenced by the average results of expert validation of 96% and 90% with very valid criteria. The Civics module has Islamic values. The material of Rights and Obligations developed has met the practical criteria. This is evidenced by the results of the questionnaire from the small group trial. The score is 86.34% with very practical criteria. From the small group trial, it was concluded that the module developed was very valid and practical.